DOI: 10.11606/t.22.2013.tde-26092013-193814
|View full text |Cite
|
Sign up to set email alerts
|

Estado de saúde e adesão ao tratamento de pacientes atendidos em ambulatório especializado em anticoagulação oral

Abstract: Dedico este trabalho especialmente à minha família: Aos meus pais, Jair e Cida: Por todos os ensinamentos e exemplos que me deram e que fizeram de mim quem hoje sou. A vocês meu eterno amor e gratidão, por tudo o que são e representam em minha vida. Aos meus irmãos, Luiz Fernando e Adriana: Pela amizade, carinho e companheirismo de sempre. Obrigada pelo apoio incondicional! Aos meus amados sobrinhos e afilhados, Amanda, Nando, Gabi, Duda, Rafa e Lucas: Vocês fazem parte do que há de melhor em mim. A felicidade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
8

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 47 publications
1
6
0
8
Order By: Relevance
“…In the meantime, there are factors that can interfere with adherence to treatment, such as advanced age, socioeconomic factors, fear of possible complications, low level of education, the need for the drug intake every day, recurrent ambulatory monitoring, food and drug interaction, self-perceived health status [3,24] corroborating the findings of this research, where clinical and socioeconomic factors were found to be more prevalent.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In the meantime, there are factors that can interfere with adherence to treatment, such as advanced age, socioeconomic factors, fear of possible complications, low level of education, the need for the drug intake every day, recurrent ambulatory monitoring, food and drug interaction, self-perceived health status [3,24] corroborating the findings of this research, where clinical and socioeconomic factors were found to be more prevalent.…”
Section: Discussionsupporting
confidence: 73%
“…[21] According to the World Health Organization, the nonadherence to long-term therapies in developed countries is around 50%, and this percentage in developing countries is higher. [22] A study conducted at the state hospital in Ribeirão Preto assessing the adherence to treatment of OAT in patients treated at a specialized anticoagulation outpatient, two months after hospital discharge, through an instrument called measure of adherence to treatment (MAT), all participants classified as compliant [3], in contrast with the results of this review.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations